International Thermal Operations and Heavy Oil Symposium 1997
DOI: 10.2118/37521-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steam Assisted Gravity Drainage (SAGD) In Horizontal Wells: A Visualization Model Study

Abstract: The successful testing of a gravity drainage process, using the horizontal wells in the Underground Test Facility (UTF) in Alberta, Canada indicates that high recovery and economical oil-steam ratios are achievable. However, several major technical challenges must be resolved to extend this successful pilot experience to commercial operations and to the many different heavy oil and extra-heavy oil reservoirs. This paper provides a consistent package of experimental data on the development of gravity drainage u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Mukherjee et al (1994) observed that the presence of low permeability zone between the injector and producer may cause water hold up between the wells where water is not well drained. Nasr et al (1997) tested 2D sand packed model that low permeability reservoirs, the steam zone was localized around the injector. The low permeability reduced the drainage of oil and growth of the gravity cell.…”
Section: Permeabilitymentioning
confidence: 99%
“…Mukherjee et al (1994) observed that the presence of low permeability zone between the injector and producer may cause water hold up between the wells where water is not well drained. Nasr et al (1997) tested 2D sand packed model that low permeability reservoirs, the steam zone was localized around the injector. The low permeability reduced the drainage of oil and growth of the gravity cell.…”
Section: Permeabilitymentioning
confidence: 99%
“…It also impedes the oil flow and the growth of a steam chamber (Mukherjee et al, 1994). Nasr et al (1997) observed an increase in SOR with the reducing permeability by numerical simulation. In addition, Butler (1991) suggested to inject steam in an area with a higher permeability.…”
Section: Influencing Factors During Sagd Processmentioning
confidence: 78%
“…They also observed that fining upward sequence showed better SAGD performance due to lateral steam propagation (cupcake growth). Nasr et al (1997) reported from 2D sand packed model that for low permeability reservoirs, the steam zone was localized around the injection well. The low permeability reduced the drainage of oil and growth of the gravity cell.…”
Section: Permeabilitymentioning
confidence: 99%
“…They commented on its impact as presenting inadequate scaling of capillary pressure (Nasr et al, 1996). Using a 2D sand packed model, Nasr et al (1997) reported that transition from initialization (injection in both wells) to developed SAGD (upper well injection, lower well production) resulted in a temporary cooling of wells and drop in production. This phenomenon is more observed during the laboratory experiments with sand packed models than what actually happens in the field, since heat poor model insulation can cause such pitfalls.…”
Section: Experimental Pitfallsmentioning
confidence: 99%